UPAYA MENINGKATKAN KETERAMPILAN MENGGOSOK GIGI MELALUI VIDEO PADA ANAK TUNAGRAHITA TINGKAT SEDANG (Single Subject Research Kelas VI di SLB N 01 Padang) - RIANTI NOVTASARI (Jurnal Penelitian Pendidikan Khusus, 2015)
AbstractThis research derived from the problems was found in the class D.VI.C1 of SLB N 01 Padang showing that a student with medium mental retardation got difficulties to brush teeth. This was an experimental research which used Single Subject Research method and A-B design. Results of study it was conclude that the hypothesis was accepted indicating that the use of video could increase the ability of student with medium mental retardation to brush teeth.Keyword : Medium mental retardation: Video: Brushing teeth skill